Application of Saw Method in Determining WFH Web-based - Taufik Akbar, Muhammad (Journal of Computer Science and Informatics Engineering, 2022)
Working from home (WFH) is a modern concept during the current pandemic where employees can do their jobs from home. (WFH) can help employees provide work-life balance for employees to help companies complete their work. Working remotely or telecommuting can illustrate that employees will be able to work from home (WFH). This research process uses a decision support system to determine and select the performance of employees who get bonuses, The process of decision support systems through the criteria and weights used are = Age (0.25%), Employees who experience Covid-19 (30%), Employees residing live in the covid-19 alert zone (20%), employees who have a history of traveling from abroad (25%). The author’s purpose for this research is for employees who get work from home (WFH), by using the Simple Additive Weighting (SAW) method. for the Best Decision Support System (WFH). In this research, the method that we do is by collecting data from library research, observation. a decision support system for employees who receive (WFH), by using the simple additive weighting (SAW) method to assist decision-making in determining which employees deserve the best work from home (WFH). (WFH) is an activity to work remotely or (WFH) ) during the current covid-19 pandemic